Autoimmune diseases related to anti-N-methyl-D-aspartate receptor encephalitis, a descriptive study in a third level center - Gómez-Piña, Juan José; Rodriguez Chavez, Emanuel; Vera Lastra , Olga Lidia (International Journal of Research in Medical Sciences, 2023)
Background: Epiphenomena in neurological disorders can lead to subsequent autoimmune diseases such as autoimmune encephalitis (AE), but research on this condition is limited. There is a lack of knowledge about the development of autoimmune diseases in AE patients due to its rarity. The objective of this study is to investigate the association between the development of autoimmune diseases and patients with anti-NMDA autoimmune encephalitis. Methods: A cross-sectional study was conducted from 2015 to 2022 at UMAE La Raza Antonio Fraga Mouret to investigate the relationship between autoimmune diseases and anti-NMDA AE. 194 patients were tested for anti-NMDA antibodies in cerebrospinal fluid (CSF), and 50 were found to meet the criteria for AE based on clinical, laboratory, and imaging tests. Follow-up evaluations assessed for rheumatological diseases and various additional tests were conducted before and after the AE event. The study was approved by the ethical and investigation committee. Results: Our analysis included 50 patients with autoimmune encephalitis. Of these, 62% were women aged 18-51 years (mean age 31.97 years) and 38% were men aged 19-72 years (mean age 39.2 years). Fifty-two percent of patients had positive antibodies for autoimmune diseases, but only 12% met ACR criteria for autoimmune disease. The CSF was negative for infections. Electroencephelography (EEG) showed abnormalities in 42% of patients, and Magnetic resonance imaging (MRI) showed hyperintensity in the medial temporal lobes, cortico-subcortical regions, and white matter. False positives were excluded. Conclusions: Among patients with autoimmune encephalitis, 12% had associated autoimmune diseases, most of which developed after the diagnosis of encephalitis. The observed diseases were 3 cases of lupus, 1 of rheumatoid arthritis, 1 of thyroiditis, and 1 of vasculitis. There is an epiphenomenal relationship between autoimmune encephalitis and subsequent development of autoimmune diseases.